DOES BEAUTY MATTER IN UNDERGRADUATE EDUCATION? - Deryugina, Tatyana; Shurchkov, Olga (Economic Inquiry, 2015)
Physically attractive individuals achieve greater success in terms of earnings and status than those who are less attractive. However, whether this 'beauty premium' arises primarily because of differences in ability or confidence, bias, or sorting remains unknown. We use a rich dataset from a women's college to evaluate each of these three mechanisms at the college level. We find that students judged to be more attractive perform significantly worse on standardized tests but, conditional on test scores, are not evaluated more favorably at the point of admission, suggesting that more attractive people do not possess greater abilities at the beginning of college. Controlling for test scores, more attractive students receive only marginally better grades in some specifications, and the magnitudes of the differences are very small. Finally, there is substantial beauty-based sorting into areas of study and occupations. ( JEL J16, I21, I23)